Effect of growth stoichiometry on the structural properties of AlN films on thermally nitrided sapphire (1120). Issue 3 (16th December 2013) - Ueno, Kohei; Kishikawa, Eiji; Inoue, Shigeru; Ohta, Jitsuo; Fujioka, Hiroshi; Oshima, Masaharu; Fukuyama, Hiroyuki
Abstract High‐quality AlN epilayers were grown via pulsed sputtering deposition on thermally nitrided sapphire <![CDATA[(1120)]]> <inline-graphic xlink:href="ark:/27927/pgg4sxz8f6q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> with precise control of the N/Al ratio. Under slightly Al‐rich growth conditions, the growth of AlN epilayers on the thermally nitrided sapphire proceeded in a two‐dimensional mode from the initial stage of growth, and their surfaces were atomically flat stepped and terraced structures. The FWHM values of the X‐ray rocking curves were as low as 87 arcsec and 339 arcsec for the 0002 and <![CDATA[1 102]]> <inline-graphic xlink:href="ark:/27927/pgg4sxz8f4m" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> diffractions, respectively, at a film thickness of 400 nm. The present approach is therefore quite promising for the low‐cost fabrication of AlGaN‐based UV optical devices. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)